High strength oil palm shell concrete beams reinforced with steel fibres - Yap, S.P. (Consejo Superior de Investigaciones Científicas, 2017)
The utilization of lightweight oil palm shell to produce high strength lightweight sustainable material has led many researchers towards its commercialization as structural concrete. However, the low tensile strength of Oil Palm Shell Concrete (OPSC) has hindered its development. This study aims to enhance the mechanical properties and flexural behaviours of OPSC by the addition of steel fibres of up to 3% by volume, to produce oil palm shell fibre-reinforced concrete (OPSFRC). The experimental results showed that the steel fibres significantly enhanced the mechanical properties of OPSFRC. The highest compressive strength, splitting tensile and flexural strengths of 55, 11.0 and 18.5 MPa, respectively, were achieved in the OPSFRC mix reinforced with 3% steel fibres. In addition, the flexural beam testing on OPSFRC beams with 3% steel fibres showed that the steel fibre reinforcement up to 3% produced notable increments in the moment capacity and crack resistance of OPSFRC beams, but accompanied by reduction in the ductility.